Incidencia de los géneros periodísticos en el proceso de formación de los estudiantes en la carrera de Comunicación Social de la Universidad Técnica de Babahoyo Extensión Quevedo, año 2021 - Ochoa Icaza, Jomaira Yuleydi (2022)
Journalistic genres are appropriate when it comes to providing information to the community through the journalist's part, which is why it has become an indispensable tool for developing communication messages that can even change behavior, for example, by influencing the listener audience decisions. It seeks to practice journalistic genres by selecting the starting point for the study acquired in the work environment. For this reason, a disposition of students of the training process on the journalistic genres of the students of the social communication career of the Technical University of Babahoyo Extension Quevedo is detailed. Reality provides the journalist with a wide range of content, with which it is possible to discern its importance for the people he writes about. Finally, our findings together with the previous section will reveal answers to our previous questions and we will be able to determine where the news and electronic newspapers are printed.